Landfill Leachate Treatment Using Nano Composite Adsorbent - Zulkifly, Natasha Amiera Mohd (Universiti Sains Malaysia, 2017)
Adsorption via activated carbon (AC) is one of the best methods to treat stabilized landfill leachate. However, this technique required high cost and limited resource of AC precursor. Thus, aim of this research is to develop new composite media which could reduce the cost yet effectively remove the contaminants of landfill leachate. In this study, sugarcane bagasse, a cheap and abundant biomass from agricultural waste was used as activated carbon media. The prepared sugarcane bagasse activated carbon (SBAC) was tested for color, chemical oxygen demand (COD), and ammoniacal nitrogen (NH3-N) removals from anaerobic stabilized landfill leachate. Sugarcane bagasse activated carbon (SBAC) was prepared using chemical activation and characterized for its surface area, surface morphology, and functional groups. The performance of the adsorbent was examined in a batch mode study by varying the shaking speed, contact time, adsorbent dosage, and pH. The experimental results indicated that SBAC could adsorb and remove the pollutants from anaerobic municipal stabilized landfill. Removal of color, COD, and NH3-N were favorably described by Freundlich isotherm. The experimental results revealed that the optimum experimental conditions (e.g. 200 rpm shaking speed, 60 min contact time, 2 g AC dosage, and pH 4) resulted in 96.36%, 72.56%, and 92.36% removal of color, COD, and NH3-N, respectively. It was indicated that the sugarcane bagasse activated carbon able to act as media in landfill leachate treatment.